Supporting collaborative learning by scaffolded meetings in the university programming courses - Saaririnne, Anni-Maria (2024)
Hundreds of students sign up for programming courses in the hopes of getting credits on their certificates and an advantage in the job market. However, the pass rate for the course that challenges perseverance varies between 52% and 69%. This study presents information about collaboration advantages and challenges in an undergraduate programming course. Groups were supported by the six scaffolded meetings to tackle the dropout rates.